Healthy lifestyles and noncommunicable diseases: Nutrition, the life‐course, and health promotion - Marlon E. Cerf (Wiley, 2021)
Abstract Cardiovascular disease, cancer, diabetes, and chronic respiratory diseases, targeted by Sustainable Development Goal 3.4, afflict millions of people and account for the highest global morbidity and mortality. Obesity is associated with noncommunicable diseases. Globally, diets have become sweeter, saltier with higher fat content, whereas physical activity has declined; which triggers the onset of obesity and noncommunicable diseases. Healthy nutrition and regular exercise are the foundations for healthy living and important for preventing noncommunicable diseases, in alignment with health promotion. The preconception, gestational, and lactational periods present windows for improving and optimizing progeny growth and development for better health outcomes. Malnutrition is a major risk factor for noncommunicable diseases; therefore ingesting healthy nutritious food, over the life‐course, is critical for countering these global epidemics that have a more profound adverse impact on people from low‐ and middle‐income countries. To combat obesity and noncommunicable diseases, people's ownership of their health, government action, and private sector responsibility should be aligned and supported by global initiatives and enabled through partnerships and collaborations. Many noncommunicable diseases are avertable through health promotion strategies mainly directed at the maternal and child health lifecycle, by focusing on women of reproductive age (prior to and during pregnancy, and during lactation) and during infancy and childhood, adolescence, adulthood, and ageing. Healthy lifestyles support health promotion and disease prevention, which is cost‐effective for noncommunicable diseases. The global high burden of obesity and noncommunicable diseases remains a complex and prevalent challenge; therefore, the adoption of healthy lifestyles is critical to slow down their onset and exacerbation.